Peningkatan Kapasitas Petani Melalui Pengendalian Hama Dan Penyakit Dan Pemanfaatan Pekarangan Rumah Berbasis Potensi Lokal Di Kelurahan Kambo - M. Zainal S; Chitra Astari; Ervianingsih Ervianingsih; Eghy Andriani Achmad; Herika Hamka; Sulistiyaningsi Sulistiyaningsi; Mustafa Mustafa; L.M. Almufakhir Idris; Andi Suprianto (Universitas Mathla'ul Anwar Banten, 2022)
INCREASING CAPACITY OF FARMERS THROUGH PEST AND DISEASE CONTROL AND UTILIZATION OF HOME YARDS BASED ON LOCAL POTENTIAL IN CAMBO VILLAGE. Kambo Village is one of the agricultural and plantation commodities (durian, langsat, rambutan, cloves, cocoa, pepper, lemongrass, galangal and kecomrang). However, the problem experienced is the lack of guidance and assistance activities related to the types of commodities being cultivated, which impact the productivity of agricultural things that are relatively not optimal. The purpose of the activity is to produce capacity building activities through counselling and assistance in controlling pests and diseases of plantation crops (cloves and durian) and short-term crop cultivation (vegetables) in utilizing home yardland. The method used is lecture, discussion and direct practice. The preparation of activities was carried out by inviting community representatives who were members of farmer groups and women's farmer groups. The selected activity participants are then coordinated with the village government to facilitate the program's implementation. The benefits felt by the participants after participating in the activity were an increase in knowledge, understanding and skills both in terms of controlling clove and durian plant pests and vegetable cultivation techniques in the context of utilizing the gardens of the members of the farmers' houses.